2005
DOI: 10.1097/01.ta.0000124279.08072.f5
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Infection in Trauma Patients: Where Do We Stand?

Abstract: HP patients had more preexisting conditions and complications than controls. There was no difference in overall mortality between the two groups. However, pulmonary/infectious complications were associated with significant mortality in HP patients. HP patients consumed more health care resources than controls, as exemplified by greater ILOS and HLOS and more operative procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…Concerns have been raised that HIV-infected patients have longer hospital stays and greater follow-up, affecting outcomes [31,32]. In fact, in our study, HIV seropositive patients were observed to stay significantly longer in the wards as compared to HIV seronegative patients.…”
Section: Discussionmentioning
confidence: 49%
“…Concerns have been raised that HIV-infected patients have longer hospital stays and greater follow-up, affecting outcomes [31,32]. In fact, in our study, HIV seropositive patients were observed to stay significantly longer in the wards as compared to HIV seronegative patients.…”
Section: Discussionmentioning
confidence: 49%
“…35,36 We found nearly identical numbers of hospital days and surgical follow-up visits in HIVinfected and HIV-noninfected patients.…”
Section: Commentmentioning
confidence: 63%
“…In burn patients no differences have been found in outcome 10 whereas in open fractures, more infections occurred. 11 In the largest retrospective series to date Stawicki et al 12 compared treatment and outcomes between trauma patients with and without HIV. Unlike our population, they had significantly more comorbidities and more penetrating trauma in the HIV-positive group.…”
Section: Discussionmentioning
confidence: 99%